(untitled) - Moore, Patrick (New York, 1968)
Contents: Foreword, astronomy as a hobby, the unfolding universe, telecopes and observatories, the solar system, the sun, the moon, occulations and eclipses, aurorae and the zodiacal light.
Keywords: Astronomy,Thiên văn học